2012
DOI: 10.1021/ef301295k
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Emissions from Wood Combustion. Part 1: Emission Factors and Characteristics from Different Small-Scale Residential Heating Appliances Considering Particulate Matter and Polycyclic Aromatic Hydrocarbon (PAH)-Related Toxicological Potential of Particle-Bound Organic Species

Abstract: An investigation was performed to study the emissions of state of the art small-scale residential heating appliances. The different combustion systems were compared at optimal combustion conditions. A comprehensive characterization of released organic species of all combustion systems was performed. An approach was performed to estimate the toxicity of the emitted particulate matter by the content of polycyclic aromatic hydrocarbons (PAHs). It is based on the proposal of the German Research Foundation (DFG) th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
85
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 111 publications
(105 citation statements)
references
References 45 publications
17
85
1
2
Order By: Relevance
“…Cellulose decomposes at temperatures >300 C yielding source specific molecular tracers mainly levoglucosan, mannosan, and galactosan (Orasche et al, 2012;Schauer et al, 2001). Levoglucosan has been described as a tracer for biomass combustion from any cellulosic material .…”
Section: Anhydrous Sugarsmentioning
confidence: 99%
“…Cellulose decomposes at temperatures >300 C yielding source specific molecular tracers mainly levoglucosan, mannosan, and galactosan (Orasche et al, 2012;Schauer et al, 2001). Levoglucosan has been described as a tracer for biomass combustion from any cellulosic material .…”
Section: Anhydrous Sugarsmentioning
confidence: 99%
“…Dieser Unterschied stellte sich aber als statistisch nicht signifikant heraus, bedingt durch die hohe Variation der Emissionen beim Kaminofen und der aufwandsbedingten geringen Anzahl an Wiederholungsversuchen. Bei Experimenten mit 3,3-facher Überladung des Brennraumes mit Buchenholzscheiten (ohne Rinde) machten PAKs einen Anteil von bis zu 15 % des organischen Aerosolanteils aus, während bei normaler Beschickung "nur" 4 % PAKs entstehen (Bruns et al 2015 Weitere detailliertere Ergebnisse aus dem Teilprojekt sind zu finden bei Orasche (2013), Orasche et al (2012Orasche et al ( , 2013, Elsasser et al (2013) Kap. 3.5.4.2), in denen sich ein Befragter überzeugt zeigte, dass das EEG entscheidend für den ausbleibenden Erfolg oder gar die Umsetzung von regulierenden Maßnahmen mitverantwortlich ist.…”
Section: Sortenunterschiede Bei Zucker-und Energierübenunclassified
“…The presence of MAs has been demonstrated in emissions from wood combustion Fine et al, 2001;Nolte et al, 2001;Schmidl et al, 2008;Frey et al, 2009;Gonçalves et al, , 2011Orasche et al, 2012) as well as from wildfires, prescribed and agricultural fires (dos Santos et al, 2002;Gao et al, 2003;Sillanpää et al, 2005;Mazzoleni et al, 2007;Sullivan et al, 2008;Alves et al, 2010;Saarnio et al, 2010a;Vicente et al, 2012;Wang et al, 2011). Recently, it has been shown that combustion of peat (Iinuma et al, 2007;Kourtchev et al, 2011) as well as of certain types of brown coal (Fabbri et al, 2009) could be additional sources of ambient aerosol concentrations of MAs in regions where such fuels are utilised.…”
Section: Introductionmentioning
confidence: 99%
“…it has been used to estimate the impact from combustion of different wood types; however, no clear picture of the variability of MAs concentrations and ratios from wood combustion has been found. Some studies have reported a high variability depending on burning conditions or type of wood with filtration-based sampling (Schmidl et al, 2008;Orasche et al, 2012Orasche et al, , 2013 or by application of aerosol mass spectrometry (Weimer et al, 2008;Elsasser et al, 2013). Other studies have shown relatively little variation in MAs emissions during wood combustion under varying conditions (Jordan and Seen, 2005;Frey et al, 2009) or with different types of wood (Fine et al, 2001(Fine et al, , 2002(Fine et al, , 2004.…”
Section: Introductionmentioning
confidence: 99%